SP0100 How to select the most appropriate capillaroscopic device: pros and cons. (15th June 2017) - Hermann, W
Abstract : One of the most important indications for performing capillaroscopy is to differentiate between primary and secondary Raynaud's syndrome. Different kinds of microscopes are at hand and generally vary in terms of picture quality or price. Before purchasing a microscope and capillaroscopy software, several considerations about the required standards of examination should be made; some of which are summarized as follows: The region of interest (ROI). Normal capillaries have a mean diameter of about 8 μm. For an accurate assessment a magnification of 100–200x is recommended, for an overview the magnification of 50x is sufficient. Measurement. Beside qualitative measures like changes in vessel architecture, there should be the possibility of quantifying the number of capillaries/mm or vessel diameters. Documentation. All parts of the examination have to be stored and assigned to patient and case. Practical aspects and handling of the device. Different kinds of microscopes are on the market of which three will be discussed in detail. Briefly summarized: Stereo microscopes. Advantages: Very good image quality, zooming in and out without problems, relatively easy to use. Disadvantages: device is not mobile, in patients with finger contractures examinations are difficult to perform, relatively high costs. Videocapillaroscopes: Advantages: Very good image quality, easy to use, "gold standard" for capillaroscopy. Disadvantages: No overview, zooming in and out not applicable (change of lenses required), relatively high costs. USB microscopes: Advantages: low costs, zooming in and out without problems, easy to use. Disadvantages: limited picture quality, documentation laborious. Selecting a capillaroscopic device depends on the conditions of use ("quick look" vs. "academic evaluation and follow up"), which should be clarified before buying a device. The price range is significant and usually differs between 100€ for USB microscopes and up to 10, 000€ for stereo and videocapillaroscopes Literature: Cutolo M et al. How to perform and interpret capillaroscopy. Best Pract Res Clin Rheumatol. 2013;27(2):237–48. Cutolo M et al. State of the art on nailfold capillaroscopy: a reliable diagnostic tool and putative biomarker in rheumatology? Rheumatology (Oxford). 2013;52(11):1933–40. Disclosure of Interest: None declared